DIMENSI PENGAMALAN DALAM NOVEL AMONGRAGA & TEMBANGLARAS KARYA ARDIAN KRESNA (KAJIAN SOSIOLOGI SASTRA) - Nurlaili Rafiah (STKIP PGRI Jombang, 2020)
Amongraga & Tembanglaras novel is one of the very interesting literary works to be studied because this novel contains a lot of religious values illustrated from the attitudes of the characters contained in the story for example, mutual assistance, behaving honestly and politely to anyone. We can apply this attitude in social life. This study aims to find and describe the attitudes or behaviors of people who are motivated by the teachings of their religion shown in attitudes and behavior in social life for example, helping one another, being honest and polite. The method used in this study is a qualitative approach that is supported by data collection using document or library techniques. The data source in this research is Novel Amongraga & Tembanglaras Karya Ardian Kresna. Data analysis techniques in this study use the concept of hermeneutics by taking steps namely, reading, marking, coding, analyzing. The results of the study showed that in the novel Amongraga & Tembanglaras depicted many positive attitudes and behaviors shown by good deeds, friendly, and polite to anyone and can be used as an example in daily life.